Assessment of Serum Lipid Profiles and Kidney Function in Patients with Type 2 Diabetes - Nasser, Zainab Abdul Abbas; Abbas, Hadeel Mohsen; kadhom, Eman Habib (Medical Science Journal for Advance Research, 2026)
The research study was carried out in the Diabetes and Endocrinology Center of Al-Sadr Teaching Hospital in Najaf, Iraq, to examine how the lipid profiles of patients with Type 2 Diabetes have changed since 2025–10–1 to 2026–2–30. The characteristics of 25 healthy subjects (with no health conditions) were compared to the characteristics of the 50 Types 2 Diabetic patients. Glucose levels were assessed and the serum lipid profiles were assessed in terms of TC (total cholesterol), TG (triglycerides), HDL (high-density lipoproteins), LDL (low-density lipoproteins), and VLDL (very low-density lipoproteins), as well as urea and creatinine. The findings showed that the glucose levels in diabetic patients were statistically significantly higher (p < 0.01) than those of the normal group. and the serum lipid profile levels (TC, TG, LDL, VLDL) were also statistically significantly greater (p < 0.01) in the Type 2 Diabetic patients compared to the healthy group. When compared with the control (healthy) group, the HDL measurement of the lipid profile appears significantly less (p < 0.01) for type 2 diabetic patients in a serum sample. Additionally, type ii diabetic patients demonstrated very high levels (p < 0.01) of both urea and creatinine concentrations (measured via blood draw) compared to non-diabetic control subjects. As such, these data support the proposition that diabetes has an adverse effect on both serum lipid profile and kidney function relative to subjects without diabetes.